Quantitative methods in budgeting - Tilanus, C. B. (Leiden : Martinus Nijhoff, 1976)
This book tries to strengthen the ties between, on the one hand, the business administration and accounting world and, on the other, the operational research and management science world.
Includes bibliographical references and index.
hza 27/09/2018
Loans
Keywords: Budget in business